AB1077 Treatment Patterns and Persistence with Subcutaneous Biologic Therapies in Patients with Ankylosing Spondylitis. (10th June 2014) - Govoni, M.; Lyu, R.; Ding, Q.; Fan, T.; Ogbonnaya, A.; Donga, P.; Korn, J.; Makin, C.
Abstract : Background: Ankylosing Spondylitis (AS) is a chronic, systemic disease that predominantly affects the axial skeleton with sacroiliac joints involvement as its hallmark, causing characteristic inflammatory back pain and resulting in varying degree of structural and functional impairments. Subcutaneous biologic therapies are usually prescribed to patients with active severe AS, who have responded inadequately to conventional therapy. Objectives: This study was conducted to describe treatment patterns including treatment persistence with subcutaneous biologics among newly treated AS patients over 12 months. Methods: This was a retrospective analysis using IMS Disease Analyzer-Germany, an electronic medical records database. Adult (≥18 years of age) AS patients who had no biologic experience and initiated therapy with subcutaneous biologics between January 1, 2009 and June 30, 2012 were included in the analysis. The date of the first subcutaneous biologic prescription served as their index date. Continuous observation of at least 12 months pre- and post-index date was required. Patients who were prescribed any biologic (subcutaneous or intravenous) during the pre-index period or diagnosed with rheumatoid arthritis, psoriatic arthritis or other conditions treated with subcutaneous biologics either in pre- or post-index were excluded from the study population. Persistence with index subcutaneous biologic was defined as time from index subcutaneous biologic treatment initiation until index subcutaneous biologic treatment discontinuation (continuous ≥60-day lapse in medication coverage). Switching and dose escalation patterns of the index subcutaneous biologic agents were also assessed. Results: The study cohort included a total of 108 AS patients who had no biologic experience. The mean (SD) age of the patients was 42 (12) years, with 70% of patients being male. The majority of patients (61%) indexed on adalimumab, while the remainder indexed on etanercept (28%) and golimumab (11%). NSAIDs/analgesics (67%) were the most commonly used medications in pre-index period, followed by corticosteroids (35%) and DMARDs or other immunosuppressive agents (23%). The most frequent comorbidities were osteoporosis (11%) and hypertension (7%). About 46% of AS patients persisted on their index subcutaneous biologics for at least 12 months. About 4% of the patients switched to other subcutaneous biologics during the follow-up period. Among patients persistent on their index subcutaneous biologic, 60% had dose escalation. Conclusions: Forty-six percent of the AS patients remain on their initial subcutaneous biologic for at least 12 months in Germany. Switching between subcutaneous biologics in this cohort was uncommon. Dose escalation was common among persistent patients. Results of this study should be further explored using a larger population to identify factors that impact persistence. Disclosure of Interest: M. Govoni Employee of: Merck Sharp & Dohme Limited, R. Lyu Employee of: Merck & Co. Inc, Q. Ding: None declared, T. Fan: None declared, A. Ogbonnaya Grant/research support: Merck & Co. Inc, P. Donga Grant/research support: Merck & Co. Inc, J. Korn Grant/research support: Merck & Co. Inc, C. Makin Grant/research support: Merck & Co. Inc DOI: 10.1136/annrheumdis-2014-eular.3843